Pengaruh Knalpot Particulate Trap Berbahan Dasar Kuningan Terhadap Tingkat Kebisingan Pada Mesin Diesel Stasioner - Muhammad Fakhrurozi; Askan (Jurnal Intake : Jurnal Penelitian Ilmu Teknik dan Terapan, 2017)
The development of technology and industry has also affected the level of pollution. Side effects that are very influential on human health include the level of noise that comes out of the exhaust gas (exhaust). Sound pollution comes from either gasoline-fueled or diesel-fueled engine vehicles, especially in diesel engines. To reduce noise levels there are several ways that can be done; (1) Giving a silencer to the engine, (2) Designing a muffler on the exhaust gas line, (3) Placing the sound source in the correct position, and (4) Setting the engine operation and maintenance schedule. One way to reduce the noise level in a diesel engine is to trap a particulate trap installed in the exhaust gas (exhaust). This method can reduce the gas particles from combustion to the disposal process, so that the noise level can be reduced. The purpose of this study was to determine how much influence the installation of particulate trap made of brass metal in the exhaust of a diesel engine to the level of noise caused. This study uses a factorial type random design by varying the weight of the active ingredient of metal particulate trap 200gr, 300gr, 400g at engine speed between 900-1700rpm. The results of this study indicate that the lowest noise level is obtained from a 300 gr particulate trap ranging from 79.3 dB - 79.4 dB.